2018
DOI: 10.1002/clc.22985
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lung‐function measures on cardiovascular disease events in older adults with metabolic syndrome and diabetes

Abstract: FEV and FVC are inversely related to CVD in older adults with and without MetS, but not DM (except for CHF); however, their value in incremental risk prediction beyond standard risk factors is limited mainly to metabolically healthier persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…High concentration of PAPP-A was also demonstrated to be associated with increased number of miscarriages and fetal loss ( 24 , 25 ). Studies have also reported that women who experienced pregnancy loss were at higher risk for cardiovascular diseases and diabetes ( 10 , 14 , 26 , 27 ), which have been associated with reduced lung function ( 28 ). Moreover, decreased lung function have been linked to increased levels of markers for inflammation ( 29 ), and increasing evidence indicates that chronic inflammatory and immune responses play key roles in the pathogenesis of different forms of lung conditions, including COPD ( 15 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…High concentration of PAPP-A was also demonstrated to be associated with increased number of miscarriages and fetal loss ( 24 , 25 ). Studies have also reported that women who experienced pregnancy loss were at higher risk for cardiovascular diseases and diabetes ( 10 , 14 , 26 , 27 ), which have been associated with reduced lung function ( 28 ). Moreover, decreased lung function have been linked to increased levels of markers for inflammation ( 29 ), and increasing evidence indicates that chronic inflammatory and immune responses play key roles in the pathogenesis of different forms of lung conditions, including COPD ( 15 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…As described, the MS defines the presence of three or more components, which are related to each other for the development of various pathologies especially cardiovascular and hepatic (Katsiki, Perez-Martinez, Anagnostis, Mikhailidis, & Karagiannis, 2018;Lee et al al., 2018). The component with the highest prevalence found in the evaluated workers was the abdominal adipose tissue, in this sense, the literature states that the tissue participates in the release of different substances favoring the appearance of a proinflammatory state, insulin resistance or endothelial damage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since the Framingham study found an inverse relationship between forced vital capacity (FVC) and cardiovascular diseases in 1983 [ 8 ], several studies consistently showed an association between hypertension and impaired pulmonary function [ 9 , 10 ]. Some studies even revealed that the coexistence of hypertension and reduced lung function was associated with a higher mortality rate [ 11 , 12 ]. Although the pathologic mechanism is not entirely investigated, chronic systemic and pulmonary inflammation is being regarded as the main mechanism.…”
Section: Introductionmentioning
confidence: 99%